2021
DOI: 10.1007/s10641-021-01074-y
|View full text |Cite|
|
Sign up to set email alerts
|

Otolith Sr/Ca ratio complements Sr isotopes to reveal fish migration in large basins with heterogeneous geochemical landscapes

Abstract: The potential use of Sr/Ca and Ba/Ca ratios in fish otolith, as a complement to 87 Sr/ 86 Sr to study movements of Prochilodus lineatus, was evaluated in the La Plata Basin (South America). Water ratios were obtained from samples collected during the high and low water seasons at 42 sites across the La Plata Basin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…In comparison, Mg/Ca ratios did not show this tendency for a linear relationship between water and otolith (Strohm et al, 2017), most probably because Mg uptake is influenced by other factors (Campana, 1999). In the study of Avigliano et al (2021) this relationship could not be identified for Ba/Ca ratios neither.…”
Section: Introductionmentioning
confidence: 64%
See 2 more Smart Citations
“…In comparison, Mg/Ca ratios did not show this tendency for a linear relationship between water and otolith (Strohm et al, 2017), most probably because Mg uptake is influenced by other factors (Campana, 1999). In the study of Avigliano et al (2021) this relationship could not be identified for Ba/Ca ratios neither.…”
Section: Introductionmentioning
confidence: 64%
“…to identify natal origins of anadromous salmon species (Kennedy et al, 2000;Barnett-Johnson et al, 2008;Brennan et al, 2015b). Avigliano et al (2021) tracked migrations of a single freshwater species (Prochilodus lineatus) in riverine habitats also on a very large scale in the La Plata basin. Only rarely otolith chemistry was assessed as a potential tool for fishery management for several species on a relatively small scale including different habitat types (Zeigler and Whitledge, 2010;Radigan et al, 2018c).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Avigliano et al targeted the Sr/Ca and Ba/Ca ratios to provide complementary information on fish migration in the La Plata Basin (South America). 92 Isotope and elemental fractionations in teeth were investigated to interrogate and decipher early hominin traits, describe their habitats and diet, and investigate the uptake of anthropogenic pollution. 83,93 Isotope ratios have also been used as a pathological marker as shown by Resano et al, 94 who targeted the isotope ratios of Cu in dried urine droplets to diagnose Wilson's disease patients.…”
Section: Sector Field and Multicollector La-icp-msmentioning
confidence: 99%
“…As shown in Figure , a split-stream LA-ICP-MS/MC-ICP-MS setup provided elemental and isotopic imaging from the same sampling spot, where contrasts and deviations in isotope ratios were used to follow the age and habitat of fish. Similarly, Avigliano et al targeted the Sr/Ca and Ba/Ca ratios to provide complementary information on fish migration in the La Plata Basin (South America) …”
Section: Inductively Coupled Plasma–mass Spectromertymentioning
confidence: 99%